FRI0227 A USABILITY SURVEY OF WRIST MOUNTED DISPOSABLE HEAT PAD ON RAYNAUD'S PHENOMENON IN PATIENTS WITH CONNECTIVE TISSUE DISEASES. (2nd June 2020) - Azuma, N.; Furukawa, T.; Shima, Y.; Matsui, K.
Abstract : Background: For patients with connective tissue diseases (CTD), vasodilators are used to treat Raynaud's phenomenon (RP), they are difficult to control only by medication. Although physicians recommend the use of a portable handwarmer or gloves to patients with CTD presenting with RP, sustained heat-retention effects cannot be obtained from them because the patients' daily life-related activities prevent their continued use. Since the wrist mounted disposable heat pad maintains the degrees of freedom of the hands and fingers and can remain usable during the daily activities, we considered this heat pad as a useful and highly practical heating method for CTD patients presenting with RP. Objectives: To investigate the usability and changes in symptoms resulting from the use of the wrist mounted disposable heat pad in CTD patients presenting with RP. Methods: Subjects were 23 outpatients with CTD presenting with RP (23 females; mean age 62.6 years; mean duration following the onset of RP 10.3 years; 12 systemic sclerosis, 5 mixed connective tissue disease, 5 Sjögren's syndrome, and 1 systemic lupus erythematosus) who had used the wrist mounted disposable heat pad (put the pad in a specifically designed holder and wrap it around wrist joint (max. temperature 42 degrees Celsius, heat-retention time 6 hours)). We investigated through interviews with them the use situations, usability, and changes in RP. During their using the heat pad, medication and daily life-related precautions against RP continued to be implemented as before. Results: Many patients had no knowledge of the heat pad (n=17, 73.9%). The most common wearing time of the heat pad was 5–6 hours (n=8, 34.8%). As for scenes of wearing the heat pad, patients who wore the pad when being out of the home accounted for the highest proportion (n=16, 69.6%), and as follows: at home (n=6, 26.1%), during kitchen work (n=3, 13.0%), and during housework (n=2, 8.7%). 17 patients (73.9%) replied that usability was "good", and 18 (78.3%) replied that usability was "better" compared with conventional measures. Moreover, many patients (n=16, 69.6%) replied that RP and associated symptoms had become reduced or alleviated. No patients replied that RP and associated symptoms had become exacerbated or severer. In terms of advantages of using the heat pad, patients who replied that the site on which the pad was mounted was felt to be warm accounted for the highest proportion (n=8, 34.8%), and those who replied that sites other than where the pad was mounted (such as fingertips, hands, and arms) were also warmed accounted for virtually the same proportion (n=7, 30.4%). Over 60% of the patients (n=14, 60.9%) replied that symptoms associated with RP (skin color, cold sensation, and pain) had become reduced or disappeared. In terms of disadvantages of using the heat pad, patients who replied that it was bothersome to use the pad accounted for the highest proportion while other patients made replies referring to cost and bad appearance. No significant accident occurred and as many as 17 patients (73.9%) replied that they would like to continue to use the heat pad in the future. Conclusion: There have been few reports evaluating the usefulness of a heat pad for RP. The wrist mounted disposable heat pad was thought to be a heating method having the potential to achieve high levels of usability and practicality on CTD patients presenting with RP. Given that the heat pad alleviated RP or caused sites other than where the pad was mounted to be felt warm even though it did not directly heat the hands and fingers, the pad seemed to have usefulness attributed to the heating of the wrist. Although the heat pad seems to be an excellent method for addressing RP in patients' daily lives, we hope that this heat pad will be evaluated on a larger number of patients with the addition of objective indices. References: [1]Koscheyev VS, et al. Aviat Space Environ Med. 72: 713-719, 2001. Disclosure of Interests: Naoto Azuma: None declared, Tetsuya Furukawa: None declared, Yoshihito Shima Grant/research support from: Endowed chair funded by/accepted a researcher from Kirikai Chemical and Kobayashi Pharmaceutical., Kiyoshi Matsui Grant/research support from: Asahi Kasei Pharma, Astellas Pharma (research grants), Speakers bureau: Bristol-Myers Squibb (lecture fees)